Fabrication of SmBa0.5Sr0.5Co2O5+δ Cathode Material and Its Application for Sr- and Mg-Doped LaGaO3 Electrolyte-Supported Solid Oxide Fuel Cell. (2nd June 2015) - Lin, Tai-Nan; Lee, Ruey-Yi; Kuo, Jen-Yuan; Ishihara, Tatsumi; Hosoi, Kohei
Abstract : The layered samarium and strontium doped perovskite oxide SmBa0.5 Sr0.5 Co2 O5+δ (SBSC) was synthesized by glycine nitrate combustion process (GNC). The structure, microstructure, conductivity, coefficient of thermal expansion properties were investigated. The crystallinity of SBSC powder showed pure perovskite phase above 1000 °C according to the XRD and TGA results. With the calcination temperature increased, the crystallinity improved and the powders grew larger and agglomeration occurred. The conductivity of SBSC powders increased with elevated temperature while the coefficient of thermal expansion was 22.6 × 10 -6 K -1 . SBSC powders were utilized as cathode materials in Sr- and Mg-doped LaGaO3 (LSGM)-based electrolyte-supported solid oxide fuel cell for power performance test. The cell with structure of (NiFe + CMF) | LSGM | SBSC was operated from 700 to 800 °C with humidified H2 as a fuel and ambient air as oxidant. The maximum power densities are 550 and 170 mW cm -2 at 800 and 700 °C, respectively. The experimental results indicate that SBSC is a promising cathode material for intermediate temperature solid oxide fuel cell (IT-SOFC).